Male Circumcision and HIV Risk Behavior Among University Students in Northern Nigeria. (March 2013) - Iliyasu, Zubairu; Abubakar, Isa S.; Sani, Ibrahim H.; Jibo, Abubakar M.; Karaye, Ibraheem M.; Salihu, Hamisu M.; Aliyu, Muktar H.
Recent trials demonstrate the effectiveness of male circumcision (MC) in reducing HIV acquisition in men. However, little is known about the prevalence and acceptability of the practice in northern Nigeria. A cross-sectional study design was employed to explore knowledge and attitudes to MC among university students in Kano, Nigeria ( n = 375). Almost all respondents (98.1%) reported being circumcised ( n = 368; 95% confidence interval = 96.2% to 99.2%). There was no variation in circumcision status by age, ethnicity, religion, or marital status. Majority of the respondents were circumcised by a health worker (51.2%). Most circumcisions were performed between the ages of 5 and 10 years (57.9%) and for religious reasons (79.2%). Only 38% of the respondents ( n = 104) were aware of the role of MC in reducing HIV acquisition in heterosexual males. Three quarters of the respondents agreed that circumcised men still need to use condoms. The practice of MC is nearly universal in northern Nigeria, despite low awareness of its protective role in HIV transmission. Public health programs should seize the opportunity offered by high MC acceptance rates to integrate safe medical MC services into existing HIV/AIDS prevention initiatives.